Interaction of the adenovirus IVa2 protein with viral packaging sequences - Zhang, W; Imperiale, M J (Journal of virology, 2000)
We have demonstrated previously that the adenovirus L1 52/55-kDa protein binds to the viral IVa2 protein in infected cells. The significance of this interaction was unclear, however, based on the known functions of these two proteins: the 52/55-kDa protein is required for viral DNA packaging, while the IVa2 protein is a transactivator of the major late promoter (MLP). In this report, we have attempted to elucidate a role for each of the two proteins in the other's known function. There is no apparent effect of the 52/55-kDa protein on the interaction of the IVa2 protein with the MLP. Surprisingly, however, we found that the IVa2 protein can interact with the adenoviral packaging signal and that this interaction involves DNA sequences that have previously been demonstrated to be required for packaging.